Does Pilates Exercise Increase Physical Activity, Quality of Life, Latency, and Sleep Quantity in Middle-Aged People?. Issue 3 (December 2014) - García-Soidán, J. L.; Giraldez, V. Arufe; Zagalaz, J. Cachón; Lara-Sánchez, A. J.
This prospective study assessed the effects of a 12-wk. exercise program based on the Pilates method (2 one-hr. sessions per week) on 99 sedentary middle-aged volunteers ( M age = 47.6 yr., SD = 0.8), using an accelerometry, the Pittsburgh Sleep Quality Index, and the SF-36 questionnaire to measure changes in physical activity, quality of life, sleep latency, and quantity. The variables (quality of life, sleep latency, and quantity) were compared before and after applying the Pilates program. All of the physical and emotional components of the SF-36 questionnaire showed significant improvement, and the latency and sleep quantity also showed significant increases. The results indicate that Pilates is an accessible, interesting exercise program that can generate important changes in middle age.